Metabolite Profiling, Pharmacokinetics, and In Vitro Glucuronidation of Icaritin in Rats by Ultra-Performance Liquid Chromatography Coupled with Mass Spectrometry - Beibei Zhang; Xiaoli Chen; Rui Zhang; Fangfang Zheng; Shuzhang Du; Xiaojian Zhang (Journal of Analytical Methods in Chemistry)
Icaritin is a naturally bioactive flavonoid with several significant effects. This study aimed to clarify the metabolite profiling, pharmacokinetics, and glucuronidation of icaritin in rats. An ultra-performance liquid chromatography coupled with mass spectrometry (UPLC-MS) assay was developed and validated for qualitative and quantitative analysis of icaritin. Glucuronidation rates were determined by incubating icaritin with uridine diphosphate glucuronic acid- (UDPGA-) supplemented microsomes. Kinetic parameters were derived by appropriate model fitting. A total of 30 metabolites were identified or tentatively characterized in rat biosamples based on retention times and characteristic fragmentations, following proposed metabolic pathway which was summarized. Additionally, the pharmacokinetics parameters were investigated after oral administration of icaritin. Moreover, icaritin glucuronidation in rat liver microsomes was efficient with CLint (the intrinsic clearance) values of 1.12 and 1.56 mL/min/mg for icaritin-3-O-glucuronide and icaritin-7-O-glucuronide, respectively. Similarly, the CLint values of icaritin-3-O-glucuronide and icaritin-7-O-glucuronide in rat intestine microsomes (RIM) were 1.45 and 0.86 mL/min/mg, respectively. Taken altogether, dehydrogenation at isopentenyl group and glycosylation and glucuronidation at the aglycone were main biotransformation process in vivo. The general tendency was that icaritin was transformed to glucuronide conjugates to be excreted from rat organism. In conclusion, these results would improve our understanding of metabolic fate of icaritin in vivo.